Control and Management of Ballast Water on Commercial Ships : Array - Baroiu, Nicușor; Chebac, Paul; Moroșanu , Georgiana-Alexandra (Journal of Danubian Studies and Research, 2021)
Following the industrialization and development of world economies, pollution factors which endanger the environment have increased to an alarming degree. Therefore, various measures have been proposed and taken by local, national and global authorities to remedy and control pollution and ecological balance. One of these measures taken worldwide to limit and prevent environmental disasters, was the decision proposed and approved by the Marine Environment Protection Committee (MEPC) at IMO (International Marine Organization) Convention in 2004 by the Ballast Water Management (BWM) Convention. Basically, new rules have been introduced on the control and management of ballast water of commercial ships. The paper presents aspects on how to control and manage ballast water in some types of commercial ships.